Smiles for Life National Oral Health Curriculum: Module 6. Fluoride Varnish - Hugh Silk; Alan B. Douglass; Melinda Clark; Mark Deutchman; Joanna Douglass; Wanda C. Gonsalves; Russell Maier; Rocio Quinonez; James W. Tysinger; A. Stevens Wrightson (Association of American Medical Colleges, 2012)
Abstract Smiles for Life Module 6, Fluoride Varnish, covers topics for health care providers who take care of children and adolescents. The module is more than simply a "how-to" for varnish teeth; the module covers a range of topics including the cause of early childhood caries (ECC), how to assess risks for ECC, how to perform a proper oral exam on children, and a discussion of the benefits, side effects and the sources of fluoride. There is a clear explanation on how to apply fluoride varnish and instruction for post procedure for parents and caregivers. The module concludes with advice for parents on the care of teeth and also tips for successfully implementing a fluoride varnish program. This module is accompanied by a video. Smiles for Life: A National Oral Health Curriculum is a product of the Working Group on Oral Health of The Society of Teachers of Family Medicine and endorsed by the American Academy of Family Physicians. Smiles for Life is the nation's most comprehensive and widely used oral health curriculum designed for primary care clinicians. The 8 module course covers the relationship of oral to systemic health, child oral health, adult oral health, dental emergencies, oral health in pregnancy, fluoride varnish, and the oral examination. The complete curriculum is web-based and is designed as an interactive educational tool for both individuals and groups from all aspects of the health care profession. It includes interactive online courses and clinical cases for individual and small group education, downloadable PowerPoint modules suitable for larger group presentations, instructional videos, and patient education materials. Free access to all materials is available at www.smilesforlifeoralhealth.org. The Smiles for Life (SFL) Curriculum including Module 5 Pregnancy and Oral Health have been endorsed by: American Academy of Family Physicians American Academy of Pediatrics Society of Teachers of Family Medicine American Academy of Physician Assistants Physician Assistant Education Association Association of Faculties of Pediatric Nurse Practitioners National Association of Pediatric Nurse Practitioners National Interprofessional Initiative on Oral Health American Association of Public Health Dentistry Gerontological Advanced Practice Nurses Association The SFL Curriculum has been downloaded from our website more than 140,000 times (www.smilesforlifeoralhealth.org) including: 58,000 courses 77,000 supplements 11,000 online courses completed The SFL Curriculum is: The core oral health curriculum used in 30+ medical schools. Utilized in most Family Medicine residency programs nationwide. Core curriculum for National Interprofessional Initiative on Oral Health. The SFL curriculum was awarded the Society of Teachers in Family Medicine (STFM) Innovative Program Award honoring excellence in development of an educational program in 2007 and received Letters of Commendation from the American Dental Association and American Academy of Family Physicians' (AAFP) Commission on Education in 2011.